KARAKTERISTIK DEMOGRAFI DENGAN SELF MANAGEMENT HIPERTENSI PADA LANSIA DI DESA U BARO KECAMATAN COT GIREK KABUPATEN ACEH UTARA - Riansyah, Ferdi; Halizasia, Gadis; Mauyah, Nizan; Maulida, Maulida; Br Karo, Dina Andriani; Husna, Asmaul (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Hypertension is a chronic disease, therefore patients must be responsible for carrying out self-management both to reduce symptoms and reduce the risk of complications. Hypertension treatment is a long process that requires strategies for managing the disease, one of which is self-management. Self-management is a strategy for people with long-term disease conditions. Self-management is a procedure for individuals to regulate their behavior. Based on the results of a field survey conducted by researchers, it was found from 13 samples who were observed through unstructured interviews that 11 of them were in the pre-elderly age period who had experienced hypertension for a long time and regularly took hypertension medication. This study aims to determine the relationship between demographic characteristics and self-management of hypertension in the elderly in U Baroh Village, Cot Girek District, North Aceh Regency. This research design will use a correlation type by taking a simultaneous approach. The population in this study was 229 elderly people in U Baroh Village, Cot Girek District, North Aceh Regency. The sampling technique used a simple random sampling technique for 70 respondents. Data analysis was carried out univariate and bivariate using the Chi-Square test. Based on the research results, show that there is a relationship between work and self-management with a p-value of 0.002 <0.05, which means there is a significant relationship between work and self-management in the elderly in U Baroh Village, Cot Girek District, North Aceh Regency.